Família e sexualidade: desafios e perspectivas à luz da Amoris Laetitia. - Teixeira, Márcio José Costa (2021)
This research aimed to identify, in light of Amoris Laetitia, challenges and perspectives to pastoral action in the current context of the family, considering the principles of the theological ethics of sexuality and marriage. It started based on the premise that, in face of the current situation of anthropological-cultural change and the complexity of the issues related to marriage and family, there is a need to explore, with freedom, some theological, moral, and pastoral questions about family and sexuality. The research had as reference the publications of Pope Francis, the studies of authors such as Marciano Vidal, Eduardo López Azpitarte and other interlocutors who were fundamental for the understanding and analysis of the data. With a qualitative approach, a bibliographic and documentary research was carried out. In considering family and sexuality based on the current challenges, it was perceived the need for pastoral advances that, without weakening Christian morals, seek to dialogue with reality. In contemporary times, while there are advances in the perception of how sexuality is conceived, the sexual dimension of the human being is exclusively associated with ways of achieving and offering pleasure, disconnected from the fundamental dimensions of the person in a relationship, which can influence a sexual behavior uncommitted to life. In the face of scientific advances and the emancipation of a liberal culture, neoconservative postures arise that signal sexuality as something to be controlled and standardized, which brings back the ethical tension about the procreative and unitive purpose of sexuality. The ecclesial vision on family and sexual morality has gone through a progressive path that, at times, has indicated setbacks when facing scientific and cultural challenges, but, in a general context, has advanced in its Christian-ethical message, considering the contributions of science and in dialogue with cultural changes. The pastoral perspective of Amoris Laetitia, revealed that sexuality is considered a dimension of the person that enables human growth in light of the law of gradualness, and it is recognized that conjugal love is a sign of humanization in view of the good of the person and therefore offers a process of growth that gives special dignity to the manifestations of body and spirit, and a gradual positive experience of the unitive purpose of sexuality or fecund conjugal love. The pastoral praxis is based on a moral theology open to all human dynamism, which allows a contextualized ethics of conjugal sexuality, not from the norm, but from the person who demands a clarification of the value of the conjugal act, as a specific program of formation of morality in their sexual acts. It is possible to have a pastoral that integrates situations of fragility by supporting people, assisting them in the formation of a moral conscience based on the reality in which they live.